Promoting awareness of pressing issues of pre-teens cases of selected school libraries in Metro Manila - Barahan, Patrick John A.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Most pre-teens who reach the age of (9) nine to (12) twelve years old start to experience pressing issues that are not commonly addressed by teachers in a school setting. Being one of the potential agents that could help pre-teens with this kind of information need, the school library has an important responsibility of providing their information needs to help them understand their situations and grow as virtuous individuals.
This study sought to know the current efforts, services and activities being done by different school libraries in Metro Manila to promote awareness regarding the pressing issues of pre-teens. The pressing issues chosen in this study focus on bullying, special people or people with disabilities, emotional abuse, broken family, and poverty.
To have a comprehensive data, the study included a school falling under each category: public-non-sectarian-co-ed, private-sectarian-non-co-ed, private-sectarian-co-ed, private-non-sectarian-co-ed. A librarian from each school library was interviewed for at least 30 minutes.
The results of the study found that the school library space and the standards for subject headings being used were both relatable for the pre-teens. Unfortunately, formal documents were not provided by the libraries for additional data and a part of their collection also did not directly imply awareness of pressing issues of pre-teens with bullying as the most prioritized and poverty is the least. There were also no activities done by school libraries because these are taken up by the guidance counsellors' initiatives.
One of the biggest hindrance for the school library's involvement in the pressing issues of pre-teens is the lack of its existence informal documents such as the Collection Development. Most school librarians become unenthusiastic since they are not mandated or aren't encouraged to create initiatives to serve the information needs of pre-teens.
Thesis (Bachelor of Library and Information Science)
Keywords: School libraries -- Philippines